ANALISIS PENENTUAN HARGA POKOK PRODUKSI AYAM BROILER PADA USAHA TERNAK LANGODAY FRESH CHICKEN (JURNAL ULET (Utility, Earning and Tax), 2024)
This research aims to determine the correct cost of production and selling price using full costing and cost-plus pricing methods. The method used is a descriptive method. This research obtained data in the form of transaction data for the 2020 period which was compiled into Langoday Fresh Chicken's financial reports. The results of Langoday Fresh Chicken's research show that the cost of production is IDR 41,744 and the correct selling price for each chicken is IDR 56,093.